WHEN HAMLET VISITED INDIA: A STUDY ON THE INDIAN PERSPECTIVE OF ADAPTING HAMLET - Dhar, Pritam (PEOPLE: International Journal of Social Sciences, 2018)
Through this article, we will explore what happens when we put William Shakespeare’s Hamlet into the Indian perspective. The play is no longer only about themes such as revenge and insanity. The recent Indian adaptations try to address contemporary socio-economic problems more importantly. Now the question that arises is the fact that why is both Hamlet the character as well as Hamlet the play still relevant in the society. The solution is simple the themes which Shakespeare has used continues to keep it in the hunt for being a readymade solution to being successful from the adaptor’s point of view. Then, there are a few more adaptations that are interesting beyond being an adaptation of the play itself. There are adaptations that look forward to present Hamlet as a next-door character. Then there are others where the focus is on Hamlet himself and the character has been dissected to various forms and shape. Like in Hamletmachine: The Images of Shakespeare in Us (2008), Hamlet has gone through a geographical shift and tries to solve issues in the contemporary Indian setting but fails miserably to relate to them. Then there are other areas where Shakespeare’s play has not been directly adapted but the adaptation has been done from another adaptation making the play even more interesting. Most of the adaptations though are done keeping in mind the middle class audience and the story has been modified in relation to the expectation of the audience. Therefore, Hamlet does not belong to the regal family in the recent adaptations like Haider (2014) and Kashmakash (2016). He is a common man like us addressing issues which are very contemporary and global as well while themes like revenge and insanity has been viewed from a different perspective providing the play with a completely new dimension in the modern day setting.